Potential of Citrullus colocynthis L. Schrad. Immature Seed Extracts as Food Preservative against a Fungal Mycotoxigenic Contaminant - Francesca Mussi; Serena Montalbano; Belsem Marzouk; Laura Arru; Meher Refifa; Zohra Marzouk; Jamil Kraiem; Francesca Degola; Annamaria Buschini (Journal of Food Quality)
The world of plant extracts and natural compounds have long been regarded as a promise land for the individuation of healthy alternatives to chemical preservatives, against microbial contamination, in food and feed commodities. A plethora of aromatic and medicinal plant species have been studied from decades to explore their antimicrobial and antioxidant properties, in order to both validate their ethnobotanical use for healing microbial illnesses and assess their suitability as food preservation agents. In fact, after terrestrialization and during the following evolutionary pathway, plants had to develop chemical compounds—constitutive and/or induced—for defence against specific pathogens, therefore becoming a potential source of new natural products usable with antimicrobial purposes. Aside from the most common contaminants that could occur in foodstuff, mycotoxigenic fungal species represent a big concern, mainly in cereals and derived products: aflatoxins in particular are the most dreaded among such toxic and cancerogenic secondary metabolites, and the control of the main producer Aspergillus flavus is currently one of the most pursued goals in the field of food safety. As aromatic and medicinal plants have a long history of use in the Mediterranean basin for both food preservation and pest control in crops, the exploitation of native species for the control of mycotoxigenic phytopathogens is almost rationale. The present work provides novel insights into the possible use of C. colocynthis seed organic extracts as antimycotoxigenic additives, demonstrating, for some of them, a feasible application as crop and food protectants with specific regard to aflatoxin contamination. Additionally, the evaluation of their cytotoxic potential and nitric oxide production on human cell lines has been reported for the first time.